2022
DOI: 10.1177/00469580221093191
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory-Descriptive Study on the Impact of COVID-19 on Teaching and Learning: The Experiences of Student Nurses in the Rural-Based Historically Disadvantaged University of South Africa

Abstract: Covid-19 has disrupted normal working conditions as people were not allowed to assemble in one place. There is a limit that is placed on the number of people congregating in public areas, and these measures also affect the education system worldwide. The purpose of the study was to explore nursing students’ experiences in a historically disadvantaged rural-based university on the impact of Covid-19 on teaching and learning. The study employed an exploratory-descriptive qualitative design among nursing students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…These comments concur with those from a study conducted by Makhado et al ( 2022 ), which reported that the introduction of a new learning modality should be accompanied by a thorough orientation of both learners and lecturers to facilitate effective learning. Lecturers must also develop innovative teaching methods and expose nursing students to clinical learning to acquire psychomotor skills and enhance their professional conduct (Shindjabuluka et al 2022 ).…”
Section: Data Collectionsupporting
confidence: 87%
See 1 more Smart Citation
“…These comments concur with those from a study conducted by Makhado et al ( 2022 ), which reported that the introduction of a new learning modality should be accompanied by a thorough orientation of both learners and lecturers to facilitate effective learning. Lecturers must also develop innovative teaching methods and expose nursing students to clinical learning to acquire psychomotor skills and enhance their professional conduct (Shindjabuluka et al 2022 ).…”
Section: Data Collectionsupporting
confidence: 87%
“…This is supported by a study conducted by Nguyen ( 2015 ), which reported that e-learning has a positive impact on the academic achievements of students in terms of reducing costs, saving time and increasing the accessibility of education, while enhancing academic performance. It was affirmed by Makhado et al ( 2022 ) that online learning was identified as a vehicle through which learners are empowered to participate at their own time and reinforce self-directed learning. Wallace et al ( 2020 ) meanwhile showed that despite the educational challenges during COVID-19, skills and creativity in nursing students increased.…”
Section: Data Collectionmentioning
confidence: 99%
“…Similarly, Shrestha et al's (2021) research showed the noticeable negative impact of the pandemic on university students' and teachers' mental wellbeing in Bangladesh and Nepal. In another study, Makhado et al (2022) reported that undergraduate students and their teachers in Kenya experienced elevated anxiety during the pandemic. However, they used several coping strategies such as online chatting with friends, watching films and participating in online vocational training to deal with the challenges.…”
Section: Literature Review Online Education During the Pandemic And R...mentioning
confidence: 99%
“…It was worsened by COVID-19 pandemic where all Universities moved from traditional face-to-face teaching and learning to modes such as emergency remote learning and online learning [6]. Prior COVID-19 pandemic, only few Universities were engaged with Blended teaching and learning and even fewer offering full online [7]. In Africa, rural-based Universities suffered the impact of COVID-19 pandemic most and South Africa was not exempted [8].…”
Section: Introductionmentioning
confidence: 99%